Preventing and Managing Radial Artery Bleeding following Transradial Procedures: Strategies and Considerations - Istianah, Istianah; Peristiowati, Yuly; Hariyono, Hariyono; Manumara, Theophylia Melisa; Sani, Miftahuddin (Universitas STRADA Indonesia, 2025)
Background: Cardiac catheterization is an invasive diagnostic procedure using one or more catheters inserted into the heart and certain blood vessels to determine the degree of narrowing in the coronary arteries. Catheterization access through the radial artery shows better results that are not free from complications of bleeding and hematoma. Purpose: To determine whether there is a relationship between the duration of mechanical compression of the radial artery and the incidence of bleeding. Methods: Quantitative cross Sectional . The sample size was 40 patients, divided into 2 groups, namely 20 respondents who in aff mechanical compression at three hours and 20 respondents at four hours. Results: Observations were made every 15 minutes in the first hour, every 30 minutes in the second hour, and every 1 hour in the following hours. Research results: The chi-square test obtained p = 0.038¸ p value ≤ α (0.05) then H0 was rejected, which is statistically interpreted as a relationship, so it can be concluded that there is a significant relationship between the duration of aff mechanical compression on the radial artery and bleeding in post-operative corangiography patient. Conclusion: There is a significant relationship between the duration of aff mechanical compression of the radial artery and bleeding in post corangiography standby PCI patients. Optimal compression duration is essential to minimize bleeding complications and improve the safety of the procedure.